Tibetan Opera: A History - Gnanasekaran, R (SOSIOHUMANIKA, 2014)
ABSTRACT: The history of Tibet can be traced back to thousand years ago, but the written history dates back to 7th century during the reign of Songtsen Gampo. The first human who appeared in the highest plateau was surrounded by mountains and forest. They were known as Tibetan. Meanwhile, Tibetan Opera reflects the past and keep the history, cultural, and religion of Tibet alive. The word âLhamoâ in Tibetan denotes Goddess. Tibetan Opera was known as âLhamoâ. Because it was believed that when Opera was first performed, there were seven ravishing girls who sang with high-pitched voice in an open air and Thang-stong rGyalpo played the accompanying cymbals and drum. The audience thought that the goddesses hailed from heaven to make a performance. Contemplated by the exquisite voice and beauty, the audience applied the name âLhamoâ to this form of performance. Thang-stong rGyalpo was the pioneer of âLhamoâ. Introducing this kind of performances was mainly for collecting funds that was necessary for the completion of building the Iron Bridge. Further, he collected seven beautiful sisters who were excellent in singing and dancing. Thang-stong rGyalpo trained the seven sisters exactly the same way as the performances of Goddess Khadoma (Dakini) whom he had seen in his vision. Thang-stong rGyalpo and the seven beautiful girls travelled and performed in various Provinces of Central Tibet appealing for funds. Since then, âLhamoâ became a theatrical performance of Tibet.KEY WORD: Tibetan opera, âLhamoâ, Goddess, performance, Thang-stong rGyalpo, Central Tibet, Dalai Lama, and Buddha.Â RESUME: âOpera Tibet: Sebuah Sejarahâ. Sejarah Tibet dapat ditelusuri kembali ke ribuan tahun yang lalu, tapi sejarah yang tertulis kembali ke abad ke-7 pada masa pemerintahan Songtsen Gampo. Manusia pertama yang muncul di dataran tertinggi dikelilingi oleh pegunungan dan hutan. Mereka dikenal sebagai orang Tibet. Sementara itu, Opera Tibet mencerminkan masa lalu dan menjaga sejarah, budaya, dan agama orang Tibet secara hidup. Kata "Lhamo" dalam bahasa Tibet menunjukkan Dewi. Opera Tibet dikenal sebagai "Lhamo". Karena diyakini bahwa ketika Opera itu pertama kali dipertunjukkan, ada tujuh gadis menggairahkan yang menyanyi dengan suara bernada tinggi di udara terbuka dan Thang-stong rGyalpo menyertainya dengan memainkan simbal dan gendang. Para penonton menyangka bahwa Dewi itu berasal dari surga untuk membuat pertunjukan. Dikontemplasikan dengan suara merdu dan keindahan, penonton mengenakan nama "Lhamo" untuk bentuk pertunjukan itu. Thang-stong rGyalpo adalah pelopor dari "Lhamo". Memperkenalkan jenis pertunjukan itu terutama untuk mengumpulkan dana yang diperlukan bagi penyelesaian bangunan Jembatan Besi. Lebih lanjut, ia mengumpulkan tujuh saudari-saudari cantik yang sangat baik dalam menyanyi dan menari. Thang-stong rGyalpo melatih tujuh saudari-saudarinya itu dengan cara yang persis sama seperti pertunjukan Dewi Khadoma (Dakini) yang telah dilihat dalam penerawangannya. Thang-stong rGyalpo dan tujuh gadis cantik itu berkeliling dan tampil dalam pertunjukan di berbagai Provinsi Tibet Tengah untuk mengumpulkan dana. Sejak itu, "Lhamo" menjadi pertunjukan teater dari Tibet.KATA KUNCI: Opera Tibet, "Lhamo", Dewi, pertunjukan, Thang-stong rGyalpo, Tibet Tengah, Dalai Lama, dan agama Buddha.About the Author: R. Gnanasekaran is a Ph.D. Scholar at the Department of Linguistics, Puducherry Institute of Linguistics and Culture, Lawspet, Puducherry 605008, India. His e-mail address is: gnanasekaranpdy@gmail.comHow to cite this article? Gnanasekaran, R. (2014). âTibetan Opera: A Historyâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7(2) November, pp.153-158. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (May 30, 2014); Revised (August 17, 2014); and Published (November 20, 2014).